The reform of the fiscal rule in Colombia (2024)
Since the promulgation of the 1991 Constitution, public spending has increased due to a series of rights that the government must guarantee to the population. According to Mauricio Cárdenas, former Minister of Finance, this situation led to an increase in these expenditures, which in the nineties of the last century led to a notable fiscal deficit and forced the government to implement a series of reforms and measures to alleviate the fiscal situation. One of these initiatives was the signing of a macroeconomic adjustment agreement with the International Monetary Fund (IMF) in 1999, which led to the formulation of the Medium-Term Fiscal Framework (MTFF) and the Medium-Term Expenditure Framework (MTEF).